Diretrizes para análise e desenvolvimento de identidade visual: contribuições para o design ergonômico - Silva, João Carlos Riccó Plácido da [UNESP]; Paschoarelli, Luis Carlos [UNESP] (My University, 2013)
Currently, too much visual information present in all media is form vehemently, for example, in print media and interfaces used for publicity in conjunction with informational design. This visual information has great influence in the lives of human beings, since the vision of these individuals is the sense most used. Studies on visual identity have not explored this issue in a satisfactory manner, favoring thus the subject of this little development projects in the area. Note the need for analyzes to enable implementation principles of projective, making them accessible to the understanding of most individuals. This study aimed to propose an evaluation of visual identities, which were analyzed by means of visual concepts of usability, design methodologies and Gestalt. We contacted design firms specializing in visual identity projects, places where interviews were conducted to collect the marks allowed for analysis. The results point to a frequent demand the employment of visual usability principles, design methodologies and design in Gestalt visual identities.

Atualmente, o excesso de informações visuais presentes em todos os meios de comunicação é constatado de forma veemente, por exemplo, nas mídias impressas e interfaces utilizadas pela publicidade, em conjunto com o design informacional. Essas informações visuais têm grande influência na vida dos seres humanos, uma vez que a visão desses indivíduos é o sentido mais empregado. Estudos sobre identidade visual não têm explorado de forma satisfatória essa problemática, favorecendo, assim, o pouco desenvolvimento desse assunto em projetos da área. Nota-se a necessidade de análises que possibilitem a implementação de princípios projetuais, tornando-os acessíveis à compreensão da maioria dos indivíduos. O presente estudo teve por objetivo propor uma avaliação de identidades visuais, as quais foram analisadas por meio dos conceitos de usabilidade visual, metodologias do design e a Gestalt. Foram contatadas empresas de design especializadas em projetos de identidade visual, lugares onde foram realizadas entrevistas que possibilitaram recolher as marcas para análise. Os resultados apontam para uma frequente demanda do emprego dos princípios de usabilidade visual, metodologias do design e Gestalt no design de identidades visuais.
Keywords: Ergonomic; Graphic design; Guidelines; Visual identities; Ergonomia; Design gráfico; Diretrizes; Identidade visual